Organic sensitizers bearing a trialkylsilyl ether group for liquid dye sensitized solar cells. (December 2015) - Pérez-Tejada, Raquel; Martínez de Baroja, Natalia; Franco, Santiago; Pellejà, Laia; Orduna, Jesús; Andreu, Raquel; Garín, Javier
Abstract: In this work we present the synthesis, optical characterization and performance of five metal-free sensitizers for dye-sensitized solar cells (DSSC). All dyes include, for the first time, a trialkylsilyl ether group in the π-conjugated bridge (a thiophene ring). The influence of different donor unities, like triarylamine (TPA), 4 H -pyranylidene and dithiafulvene has been evaluated in DSSC with a liquid I3 /I − electrolyte, obtaining the best results with the 4 H -pyranylidene moiety. The size and the position of the bulky group have a great importance in the efficiency of the final devices. In order to explain the recombination processes and electron life-time, charge extraction (CE) and transient photovoltage (TPV) experiments have been carried out. Graphical abstract: Highlights: Synthesis and characterization of organic sensitizers with a trialkylsilyloxy group on the π-spacer. DSSC efficiency was highly dependent on the size and position of the silyloxy group. Best efficiencies were obtained with the 4 H -pyranylidene, followed by TPA and dithiafulvene systems.